Physical Chemistry Essentials - Hofmann, Andreas (Springer International Publishing, 2018)
This textbook covers the fundamentals of physical chemistry, explaining the concepts in an accessible way and guiding the readers in a step-by-step manner. The contents are broadly divided into two sections: the classical physico-chemical topics (thermodynamics, kinetics, electrochemistry, transport, and catalysis), and the fabric of matter and its interactions with radiation. Particular care has been taken in the presentation of the algebraic parts of physico-chemical concepts, so that the readers can easily follow the explanations and re-work relevant discussion and derivations with pen and paper. The book is accompanied by a rich mathematical appendix. Each chapter includes a selection of (numerical) exercises and problems, so that students can practice and apply the learned topics. An appendix with solutions allows for controlling the learning success. Carefully prepared illustrative color images make this book a great support for teaching physical chemistry to undergraduate students. This textbook mainly addresses undergraduate students in life sciences, biochemistry or engineering, offering them a comprehensive and comprehensible introduction for their studies of physical chemistry. It will also appeal to undergraduate chemistry students as an accessible introduction for their physical chemistry studies.